2011
DOI: 10.1111/j.1365-2036.2011.04662.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of exclusive nutritional therapy in paediatric Crohn’s disease, comparing fractionated oral vs. continuous enteral feeding

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 32 publications
3
115
0
11
Order By: Relevance
“…Indeed, EN should be considered in appropriate patients. The challenge, however, is to know who these are: there are no trials comparing EN versus placebo; it is unclear how long exclusive EN is needed; and data are very heterogeneous with regards to response related to disease distribution [Wilschanski et al 1996;Afzal, 2009, Buchanan et al 2009, Rubio et al 2011.…”
Section: Induction Of Remission: Enteral Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, EN should be considered in appropriate patients. The challenge, however, is to know who these are: there are no trials comparing EN versus placebo; it is unclear how long exclusive EN is needed; and data are very heterogeneous with regards to response related to disease distribution [Wilschanski et al 1996;Afzal, 2009, Buchanan et al 2009, Rubio et al 2011.…”
Section: Induction Of Remission: Enteral Nutritionmentioning
confidence: 99%
“…Supported by evidence of efficacy from the paediatric literature [Rubio et al 2011], there has only been one fully published trial in adult patients with CD [Triantafillidis et al 2006]. In an uncontrolled observational study of patients with active CD given 4 weeks of exclusive Modulen IBD (Nestlé, Lausanne, Switzerland), 11 out of 29 patients were in remission [as defined by Crohn's Disease Activity Index (CDAI) < 150] and a further 8 had a response (CDAI drop > 50) [Triantafillidis et al 2006].…”
Section: Induction Of Remission: Enteral Nutritionmentioning
confidence: 99%
“…Of note, all the studies that have demonstrated mucosal healing from EEN have been after 8 weeks or more of EEN. 34,35 In addition, faecal inflammatory markers have been demonstrated to continue to fall upto 8 weeks of EEN suggesting until further evidence evolves that 8 weeks is the optimal course length based on data from current studies. 36 There is a paucity of published data describing clinical outcomes from second courses of EEN in children and whether the benefits already discussed in terms of improvements in anthropometric and inflammatory markers are reproducible in subsequent EEN courses.…”
Section: 27mentioning
confidence: 99%
“…One report has compared outcomes of EEN administration with those of formula delivered via an NG tube [23]. Eighty-five percent of the children who received EEN via NG tube were in remission after 8 weeks contrasting to 75% of the oral group.…”
Section: Delivery Of Eenmentioning
confidence: 99%
“…Rubio et al described their retrospective experience with EEN in 106 children with newly diagnosed CD. Remission was assessed after 8 weeks of EEN and was classified as a Pediatric Crohn's Disease Activity Index of <10 [23]. Overall, 81.1% of this group entered remission with EEN.…”
Section: Efficacy Of Een In Induction Of Remissionmentioning
confidence: 99%